Multi-aspect comparative analysis of JavaScript programming frameworks – React.js and Solid.js - Kryk, Jakub; Plechawska-Wójcik, Małgorzata (Journal of Computer Sciences Institute, 2025)
Every year, new frameworks and programming libraries appear on the market, trying to gain user interest by presenting their advantages over the competition. The purpose of this article was to compare many aspects of one if such modern solution, i.e. the Solid.js library with a tool recognized on the market, the React.js library, in order to be able to form an opinion on the better choice for a programmer in 2024. The comparative analysis was divided into two parts – performance and theoretical. The research showed Solid.js' performance advantage, but also highlighted its immature ecosystem and limited number of active people in the community.